Writing profiles of deaf children taught through British Sign Language - Burman, D; Nunes, T; Evans, D (John Wiley & Sons, Ltd., 2007)
Congenitally, profoundly deaf children whose first language is British Sign Language (BSL) and whose speech is largely unintelligible need to be literate to communicate effectively in a hearing society. Both spelling and writing skills of such children can be limited, to the extent that no currently available assessment method offers an adequate appraisal of their competence. Our aim was to create such an instrument to aid assessment and to support teachers in setting objectives for their deaf students' writing development. Writing samples describing the same four-picture story were collected from 29 congenitally, profoundly deaf 10-year-old users of BSL. Six experienced teachers of the deaf ranked their writing productions in five levels; the correlations between their ranks were high and significant. This indicates that the children's texts were classified reliably into categories, which could then be used for further descriptive analysis. The texts in each category were analysed qualitatively to provide descriptive profiles for each level. An indication of the concurrent validity of the profiles was obtained through significant correlations with reading comprehension measures. Future research should ascertain further the reliability and validity of this instrument and its usefulness in setting goals for improving deaf children's writing ability.